Μαρτυρίες γιὰ τὴν εἰκονομαχικὴ ἔριδα στὴν Πελοπόννησο. Προβλήματα καὶ προσεγγίσεις - ΚΟΝΤΗ, Βούλα (Byzantina Symmeikta, 1999)
Voula Konti Evidence Concerning the Iconoclastic Controversy in the Peloponnese. Problems and Approaches In the Peloponnese, the rarity of sources and the few precisely dated finds of the period from the 7th to the beginning of the 9th century, are not enough in order to shed light on the way things were in the area. Among the few data that refer to Iconoclasm in the peninsula, the most interesting ones are about Monemvasia, whose bishops seemed to have been actively involved in the iconoclastic controversy. Besides the written sources, the archaeological evidence adds little information to our knowledge on the consequences of Iconoclasm in the area. The evaluation of the evidence allows for the suggestion, that the Peloponnese and Laconia in particular -like other provinces in Byzantium- present an ambiguous attitude: there appear activities both for (bishops, arrival of exiles) and against the cult of the images (church decoration). In Appendix, the list of the bishops of Monemvasia during Iconoclasm is discussed.